2022
DOI: 10.1038/s41598-022-06775-7
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological activities of echinopsine derivatives containing acylhydrazone moiety

Abstract: Based on the broad-spectrum biological activities of echinopsine and acylhydrazones, a series of echinopsine derivatives containing acylhydrazone moieties have been designed, synthesized and their biological activities were evaluated for the first time. The bioassay results indicated that most of the compounds showed moderate to good antiviral activities against tobacco mosaic virus (TMV), among which echinopsine (I) (inactivation activity, 49.5 ± 4.4%; curative activity, 46.1 ± 1.5%; protection activity, 42.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Some antifungal properties were found for molecules bearing naturally occurring echinospine alkaloid, 1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide which was combined with substituted phenyl or heterocyclic aldehyde fragments. Two molecules, namely (E)-N ′ -(3,4-dimethoxybenzylidene)-1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide and (E)-N ′ -((1H-indol-2-yl)methylene)-1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide, caused more than 80% of S. sclerotiorum growth inhibition [55]. In the screening study, the derivatives of indole diketopiperazine with acyl hydrazones containing 4-substituted trifluoromethylbeznaldehyde and tert-butylbenzaldehyde fragment as well as 3-chloro and 2,3-dichlorobenzaldehyde fragments exhibited more than 80% and 50% of antifungal activity against S. sclerotiorum and B. cinerea, respectively [54].…”
Section: Antifungal Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some antifungal properties were found for molecules bearing naturally occurring echinospine alkaloid, 1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide which was combined with substituted phenyl or heterocyclic aldehyde fragments. Two molecules, namely (E)-N ′ -(3,4-dimethoxybenzylidene)-1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide and (E)-N ′ -((1H-indol-2-yl)methylene)-1-methyl-4-oxo-1,4-dihydroquinoline-3-carbohydrazide, caused more than 80% of S. sclerotiorum growth inhibition [55]. In the screening study, the derivatives of indole diketopiperazine with acyl hydrazones containing 4-substituted trifluoromethylbeznaldehyde and tert-butylbenzaldehyde fragment as well as 3-chloro and 2,3-dichlorobenzaldehyde fragments exhibited more than 80% and 50% of antifungal activity against S. sclerotiorum and B. cinerea, respectively [54].…”
Section: Antifungal Activitiesmentioning
confidence: 99%
“…An alkaloid from Echinops sphaerocephalus L.-echinopsine and their hydrazide-hydrazone derivative were examined as fungicidal compounds. The 4-hydroxybenzaldehyde derivative VII at a concentration of 50 µg/mL showed very good activity against phytopathogenic fungi: Sclerotinia sclerotiorum and Magnaporthe grisea [55]. The indole derivative diketopiperazine acylhydrazone and 3,5-di-tert-butyl- 4-hydroxybenzaldehyde (VIII) showed high inhibitory activity on tobacco mosaic virus (TMV), comparable to the pesticide ningnanmycin, and moderate activity on diamondback moth (Plutella xylostella) and mosquito (Culex pipiens pallens) larvae [56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, compounds 39 and 40 were designed and synthesized, and they both showed good fungicidal activity . In addition, quinolinones 41 – 44 showed good fungicidal activity. For example, compound 44 showed 89.0% inhibition against Rhizoctonia cerealis at 50 mg/L. Compounds 45 and 46 had the same scaffold structure; however, they had weaker fungicidal activity .…”
Section: Fungicidal Activitymentioning
confidence: 99%
“…Cui et al 74 designed and synthesized a series of echinocandin derivatives 68 containing an acylhydrazone moiety and performed antifungal activity assays. The results showed that the compounds exhibited weak to moderate fungicidal activity.…”
Section: Structures and Activity Of Hydrazide Derivativesmentioning
confidence: 99%